Child rape: a legal study on the need to review the current punishment / Wan Shauki Zhafiran Wan Mohamad Zain ...[et al.] - Wan Mohamad Zain, Wan Shauki Zhafiran; Syed Zulkifli, Syed Ahmad Muzzamir; Abdul Razak, Mohd Faiz Fahmy; Arafpin, Mohamad Rahimi (2011)
This project paper dealt with the punishment for child rape in Malaysia as well as the review on the current punishment for those who commits child rape as to the adequacy and effectiveness of the law. Besides discussing on punishment for child rape in Malaysia, this project paper will touch on the punishment for child rape in United Kingdom as a comparison. This project paper is divided into five main chapters; introduction of child rape, the current punishment for child rape in Malaysia, the current punishment for child rape in United Kingdom, the findings based on the questionnaires distributed and the conclusions and recommendations. The aim of this project is to research and review the current punishment in Malaysia in comparison with the punishment in United Kingdom for the same offence and analyze as to whether the system of punishment in United Kingdom could be implemented in Malaysia. It was discovered earlier in the research that there have been debates on the adequacy and effectiveness of the current punishment to cope with the increment in the number of child rape cases. As such, this project paper will also provide suggestions and recommendations towards a comprehensive punishment for child rape. We hope that this project paper will be beneficial and enlightening to readers as well as able to give awareness towards the seriousness of child rape cases in Malaysia.